An alternative phosphorylation switch in integrin β2 (CD18) tail for Dok1 binding - Gupta, Sebanti (2015)
Integrins are involved in cell migration and adhesion. A large number of proteins interact with the cytoplasmic tails of integrins. Dok1 is a negative regulator of integrin activation and it binds to the phosphorylated membrane proximal NxxY motif in a number of integrin β tails. The β tail of the β2 integrins contains a non-phosphorylatable NxxF motif. Hence it is unclear how Dok1 associates with the β2 integrins. We showed in this study using NMR and cell based analyses that residues Ser745 and Ser756 in the integrin β2 tail, which are adjacent to the NxxF motif, are required for Dok1 interaction. NMR analyses detected significant chemical shift changes and higher affinity interactions between Dok1 phospho-tyrosine binding (PTB) domain and integrin β2 tail peptide containing pSer756 compared to pSer745. The phosphorylated β2 peptide occupies the canonical ligand binding pocket of Dok1 based on the docked structure of the β2 tail-Dok1 PTB complex. Taken together, our data suggest an alternate phosphorylation switch in β2 integrins that regulates Dok1 binding. This could be important for cells of the immune system and their functions.